Besides the sizes: body and fashion in blogs - Sarturi, Letícia (2016)
The fashion blogs are important in cyberspace and conquered people interested in the fashion and beauty world. Posts offer information about the latest trends and innovations of fashion events. This article aims to analyze the content of Brazilian blogs Entre Topetes e Vinis and Blog Lalá Noleto and language of its authors, in a quest for understanding how the body and fashion are revealed. For this, uses Discourse Analysis and Content Analysis in publications from February 2014. This paper seeks the differences and similarities in the content of blogs and theirposition relative to the body.